Diphtheria case detection and carrier study of close contacts: A step towards diphtheria eradication - Shilpa R. Shah; Nisha C. Karanje (Indian Journal of Pathology and Microbiology)
Introduction: Diphtheria is an infectious disease caused by gram-positive bacilli C. diphtheriae involving nasal, pharyngeal, tonsillar, or laryngeal mucus membranes. The mortality rate is as high as 20%, with India contributing almost 78% of the world incidence. Aims and Objectives: We report a fatal case of nasopharyngeal diphtheria with carrier study in close contacts. Materials and Methods: Seven years child presented with fever, throat pain, and earache for 3 days followed by neck swelling and noisy respiration. On examination, membrane was present in the throat, which was received for Albert and Gram staining and reported as positive for C. diphtheria like organisms followed by culture. The patient was treated with ADS and antibiotics, and intensively managed, but still succumbed to death. Follow-up was done for carriage of C. diphtheriae on the throat and nasopharyngeal swabs of siblings and close contacts. It was isolated in 3 of them. Samples were processed for Gram, Albert stain, and culture. Identification, antibiotic sensitivity, and toxigenicity were done. Results and Discussion: Four samples, one from the patient and three from contacts showed the presence of gram-positive slender bacilli with cuneiform arrangement, less cellular infiltrate on the Gram stain, and the presence of few metachromatic granules in the Albert stain. C. diphtheriae was grown on Potassium Tellurite agar. Antibiogram of all isolates was similar with resistance to Erythromycin and sensitivity to Penicillin. Isolates were confirmed by PCR and ToxA gene was detected. Contacts were treated with Penicillin and repeat swabs were negative. Conclusion: Present health statistics and this study suggests, fight against diphtheria in India is far from being over. It still lurks in some remote areas. It is a need to remain vigilant, keep tracing, and treating contacts to curtail down the rate of infection. In view of the resurgence, Government has given directives to replace TT with Td in UIP. Still, a lot needs to be done.